A review on modified ZnO for the effective degradation of methylene blue and rhodamine B - Ommy Madina Abdul Halim; Nur Hafikah Mustapha; Siti Najiha Mohd Fudzi; Rahil Azhar; Nur Izzati Nabilah Zanal; Nurul Fatihah Nazua; Abu Hassan Nordin; Mohammad Saifulddin Mohd Azami; Mohd Azlan Mohd Ishak; Wan Izhan Nawawi Wan Ismail; Zuliahani Ahmad (Results in Surfaces and Interfaces)
This study focuses on the photodegradation of two pollutants, Methylene Blue (MB) and Rhodamine B (RhB) utilizing various dopants on zinc oxide (ZnO) as the photocatalyst. The photocatalysts, both with and without dopants, were consistently prepared through co-precipitation, wet impregnation, and hydrothermal techniques. Noteworthy dopants such as Silver (Ag), Copper (Cu), Manganese (Mn), Nickel Ferrite (NiFe2O4), Titanium dioxide (TiO2), Iron (Fe) and Gold (Au) were integrated into the ZnO photocatalyst to enhance its photocatalytic efficiency as thoroughly outlined in this study. The study reveals that unmodified ZnO inadequately degrades both Methylene Blue and Rhodamine B. The incorporation of various dopants into ZnO significantly enhances its photocatalytic performance, offering a viable solution for the degradation of persistent organic pollutants in wastewater. This advancement addresses critical challenges in wastewater treatment, ensuring more efficient removal of contaminants such as Methylene Blue and Rhodamine B. Furthermore, the improved photocatalytic activity aligns with the Sustainable Development Goals (SDGs), particularly Goal 6 (Clean Water and Sanitation), by contributing to sustainable and effective water purification technologies.